A Subscription Service for Automated Communication and Fair Cost Distribution in Collaborative Blockchain-based Business Processes - Schindelmann, Moritz; Klinger, Philipp; Bodendorf, Freimut (15th International Conference on Wirtschaftsinformatik (WI), 2020)
Blockchain capabilities like Ethereum Smart Contracts offer great opportunities to manage cross-organizational business processes due to their trustless and tamperproof nature. However, communication in such processes poses a major issue since there is no direct option for one participating organization to inform other collaborators about their individual progress in their impersonation as a Smart Contract. As that knowledge is vital to execute a cross-organizational process, we design a Smart Contract architecture in which participants express their progress through Blockchain events. Further, we implement a prototype that subscribes to the relevant events of one or more participants and reacts to their occurrence by triggering the subsequent step(s) of the process. Evaluation of the prototype and architecture shows that this does not only avoid unnecessary latency in process communication but also results in a fair cost distribution as each participant is only charged for the expenses of its individual actions.<br
Keywords: Blockchain; Ethereum; Business Process Management; Cross-Organizational Collaboration

Blockchain-based Cross-Organizational Execution Framework for Dynamic Integration of Process Collaborations - Klinger, Philipp; Bodendorf, Freimut (15th International Conference on Wirtschaftsinformatik (WI), 2020)
Cross-organizational business processes involving multiple participants are choreographed, thus rely on mutual trust of collaborators or need to be coordinated by a central instance. Using Smart Contracts, business processes can be executed without a mutually trusted and centralized orchestrating authority. Former Blockchain-based execution framework proposals focus on orchestration diagrams as a basis for execution. Contrary, this work focuses on BPMN process collaboration diagrams as implementation basis and makes additional transformation steps obsolete. With the herein proposed framework for execution of cross-organizational process collaborations, another approach for the implementation and execution of inter-organizational processes on a Blockchain is presented, including a voting mechanism for process deployment as well as a subscription service to facilitate process handovers between participants more efficiently. The framework is exemplified and evaluated with a use case from a large German industrial manufacturing company. <br
Keywords: Business Process Management; Blockchain; Process Collaboration; Process Execution Engine; Ethereum

Cui bono? Wozu Smart Contracts gut sind - Karzel, Daniel; Klinger, Philipp (2017)

Literature Review Linking Blockchain and Business Process Management - Lauster, Corey; Klinger, Philipp; Schwab, Nicolas; Bodendorf, Freimut (15th International Conference on Wirtschaftsinformatik (WI), 2020)
Blockchain Technology emerged recently in the area of Business Process Management and is still in its infancy. This paper analyses and evaluates the current scientific literature on the subject matter and synthesizes common topics, in order to create an understanding of the status quo. In a structured literature review, more than 300 publications were identified, of which 24 were finally selected as relevant to the cross-sectional topic of Blockchain and Business Process Management (BPM). A quantitative analysis affirms the recent upcoming of the relatively young research field and narrows the identified papers into three topic clusters, namely application areas and challenges, process architecture and design, and process-execution-related publications.
Keywords: Literature Review; Blockchain; Business Process Management

Upgradeability Concept for Collaborative Blockchain-Based Business Process Execution Framework - Klinger, Philipp; Nguyen, Huy-Long; Bodendorf, Freimut (Blockchain – ICBC 2020. ICBC 2020. Lecture Notes in Computer Science, vol 12404, 2020)
Inter-organizational business processes involve different independent participants to interact with each other to run a collaborative business process. To date, central, trusted third parties mediate between non-trusting participants adding additional process complexity as well as administrative and run costs. Recent research showed that Blockchain and Smart Contracts can replace the role of a central trusted authority in collaborative execution of processes. Smart Contracts, that represent business process logic, cannot be altered due to immutability constraints of Blockchain systems. Yet, with the help of advanced technical upgradeability concepts, upgrading contracts, therefore enabling versioning of processes on a Blockchain is possible. This paper analyzes and implements three different upgradeability concepts. The implemented patterns are evaluated with regard to an existing blockchain-based execution framework for inter-organizational business processes. Our findings suggest the Unstructured Storage Proxy pattern to be the most promising for practical use, especially regarding cost-effectiveness and minimal added complexity. The findings are derived from simulations on a real-world use case stemming from a large German electronics manufacturing company.<br
Keywords: Blockchain; Ethereum; Business process; Collaboration; Business process management system; Upgradeability; Proxy

Vom Smart Contract zur DApp - Prototyping einer Blockchain-Anwendung - Klinger, Philipp; Karzel, Daniel (2017)